Synthesis, Identification of Some New Derivatives of Oxazpine, Thiazinone and Hydroquinazoline and Evaluation of Antibacterial Activity. - Alfraiji, Redhab A. J.; Alrecabi, Zena. G.; Al-Majidi, Suaad M. H. (Iraqi Journal of Science, 2021)
This work includes synthesis of some new derivatives of Schiff bases as intermediate compounds. Through the reaction 1,4- phen ylene diamine with different aromatic aldehydes substituted by many different groups in acidic medium and absolute ethanol as a solvent to obtain the Schiff bases (1a-5a). These compounds are reacted with substituted aromatic carboxylic acids and anhydride to give three types of heterocyclic compounds. The first line includes direct reaction with maleic anhydride under certain conditions to give new derivatives of oxazpine(6b-10b). The second line includes reaction of compounds (1a-5a) with 2-mercapto benzoic acid in the presence of triethyl amine as a catalyst and dry benzene as a solvent to give new derivatives of thiazinone(11c-15c). While the third line involved reaction the Schiff bases (1a-5a) with anthranilic acid in dioxane as solvent to give new derivatives of hydroquinazoline (16d-20d). The structures of these new synthesized compounds were identified by spectral methods their [FTIR, 1HNMR, 13C-NMR] and measurements of some physical properties and some specific reactions. Furthermore the effects of synthesized compounds on some strains of bacteria were studied.